6p=66

Simple and best practice solution for 6p=66 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6p=66 equation:


Simplifying
6p = 66

Solving
6p = 66

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Divide each side by '6'.
p = 11

Simplifying
p = 11

See similar equations:

| 44x^3-12x^2+8x-24=0 | | 10x^3+21y-35x^2-6xy=0 | | 50m^3-18m=0 | | 100z^2=16 | | -7x^2+5x+12=equation | | (4x+5)(9x+9)=equation | | (4x+5)(3x-7)=equation | | x^2+7x+12.25=0.25 | | 128=r^7 | | (x^2-11x+30)(4x+16)=0 | | 6x*1=12 | | 35000.00+1680.00x=220650.00 | | 7/2x-5/x=5 | | 13v-8v-12=-5v-42 | | 27/2=135/t | | 37/8=185/n | | 6q^2+44q+48=0 | | n/4=5/8 | | 4(x-2)=3x-6 | | (18x+(2x^2)*y)dx-(x^2+4)dy=0 | | 6q^2-10q-4=0 | | 4/8=4/t | | n/4=25/5 | | 6q^2-11q-72=0 | | x/12=225/15 | | 12/16=x/24 | | 1.12= | | 12z^2+16z-28=0 | | (18+(2x^2)*y)dx-(x^2+4)dy=0 | | x/3=4-x | | 24n^2-40n+14=0 | | X^2+y^2+12x-8y+48=0 |

Equations solver categories